Are Patients with Limb and Head Tremor a Clinically Distinct Subtype of Essential Tremor?. (10th April 2015) - Lenka, Abhishek; Bhalsing, Ketaki Swapnil; Jhunjhunwala, Ketan Ramakant; Chandran, Vijay; Pal, Pramod Kumar
Abstract: Background: Essential tremor (ET) is the most common tremor disorder in adults. In addition to upper limbs, the tremor in ET may also involve head, jaw, voice, tongue, and trunk. Though head tremor (HT) is commonly present in patients with ET, large comparative studies of ET patients with HT (HT+) and without HT (HT−) are few. Methods: To determine whether ET with HT is a distinct clinical subtype by comparing ET patients with and without HT, a chart review of 234 consecutive patients with ET attending the neurology clinics of the National Institute of Mental Health and Neurosciences, India, was done. A movement disorder specialist confirmed the diagnosis of ET in all patients using the National Institutes of Health collaborative genetic criteria. Results: HT was present in 44.4% of the patients. Comparison between HT+ and HT− showed that the HT+ group patients: (1) were older, (2) had later onset of tremor, (3) had unimodal distribution of age at onset with a single peak in the fifth decade, (4) had more frequent voice tremor, and (5) were more likely to have mild cervical dystonia. HT was part of presenting symptoms in nearly two thirds of the ET patients and in the rest it was detected during clinical examination. Conclusions: Several demographic and clinical variables suggest that ET patients with HT have a distinct clinical phenotype. RÉSUMÉ: Le tremblement des membres et de la tête constitue-t-il un sous-type de tremblement essentiel? Contexte: Le tremblement essentiel (TE) est le type de tremblement le plus fréquent chez les adultes. En plus des membres supérieurs, le tremblement essentiel peut également toucher la tête, la mâchoire, la voix, la langue et le tronc. Bien que le tremblement de la tête (TT) soit présent en général chez les patients atteints de TE, il y a peu de grandes études comparatives portant sur des patients atteints de TE avec TT (TT+) et sans TT (TT-). Méthode: Nous avons effectué une revue des dossiers de 234 patients consécutifs atteints de TE suivis à la clinique de neurologie du National Institute of Mental Health and Neurosciences en Inde afin de déterminer si le TE avec TT est un sous-type clinique distinct en comparant les patients atteints de TE avec et sans TT. Résultats: Le TT était présent chez 44, 4% des patients. La comparaison entre le groupe TT+ et le groupe TT- a montré que les patients du groupe TT+ étaient plus âgés, que le début du tremblement était tardif, que la distribution de leur âge de début était unimodale avec un seul pic dans la cinquième décennie, que le tremblement de la voix était plus fréquent et qu'ils étaient plus susceptibles d'avoir une légère dystonie cervicale. Le TT faisait partie des symptômes initiaux chez presque les deux tiers des patients atteints de TE et chez les autres, il avait été détecté au cours de l'examen clinique. Conclusions: Plusieurs variables démographiques et cliniques suggèrent que les patients atteints de TE qui présentent un TT ont un phénotype clinique distinct.